RELIGIOSITY CONSCIOUSNESS AS THE FOUNDATION OF PERSONALITY IN SUFISM - Iskandar Iskandar; Ridwan Muhammad Hasan Ridwan Muhammad Hasan (Jurnal Ikhtibar Nusantara, 2024)
Consciousness as a primary mental function continues to be studied in its relationship with religiosity by experts in shaping personality. Religiosity, in the sense of earnestness in practicing religious practices in Islam, is specifically discussed in Sufism as a discipline of spirituality. This paper presents religious consciousness in shaping personality as it relates to Sufism. In Sufism, personality formation involves the stages of takhalli (identification of negative traits), tahalli (identification of positive traits), and tajalli (internalization of positive traits). The discussion combines literature data with field data from Sufi practitioners affiliated with the Naqshbandiyyah order in the northern coastal area of ​​Aceh. Sufism among the Acehnese community, particularly in the northern coastal region, remains a primary reference in understanding and strengthening religiosity, as evidenced by the religious references used in Islamic boarding schools (dayah) and among followers of the Sufi order. These references explicitly explain the relevance and significance of practicing Sharia, Tariqa, and Haqiqah as an inseparable unity. Sufism, through its references and field practices, is known to enhance religious consciousness in shaping an Islamic personality.